ASSESSING THE IMPLICATIONS OF SUPPLY CHAIN DISRUPTIONS AND PRICE VOLATILITY IN ASIAN COUNTRIES DURING THE COVID-19 PANDEMIC AND THE WAR BETWEEN RUSSIA AND UKRAINE. - M, Alshater; Yoon, S. M (Economics and Statistics Research Journal (ESRJ), 2023)
This research paper aims to investigate the impact of the ongoing Russia-Ukraine crisis on food inflation and stock market return volatility in Asian countries, specifically India, China, Japan, and Thailand. The paper intends to make a comparative analysis of the impact of the crisis on these Asian economies. The importance of the paper is justified by the ongoing war's havoc on the food systems and financial markets of many countries, especially those in the proximity of the warring nations (Russia and Ukraine). The study seeks to understand how the war impacts the functioning of their respective domains and how to shape their policies and strategies accordingly. The paper delves into the political determinants of such markets, as war in any country is bound to lead to a catastrophic chain of events that eventually dampens the growth of the country in question. The destruction of Ukraine's agriculture, industrial, and energy sectors, carried out by Russia, has resulted in a 29.1% fall in the country's GDP in 2022, impacting not just Ukraine but also neighbouring countries. The study draws on similar impacts of wars in the past, highlighting their failure to feed the growing population, rural-urban migration, rising food prices, and dependency on food imports. Such issues led to food shortages, as experienced during the global food crises of 2006-08, 2010-11, and between 2021-23, with food prices showing an increasing trend since 2003. The research paper's findings will be essential not only to policymakers but also to investors who need to make informed decisions on their investments in these countries. The paper's value approach, based on the study of wars' impact on food inflation and stock market volatility, is novel in targeting the Russia-Ukraine conflict's political determinants